2020
DOI: 10.1051/ctv/20203502063
|View full text |Cite
|
Sign up to set email alerts
|

Effects of winemaking on ‘Marselan’ red wines: volatile compounds and sensory aspects

Abstract: Winemaking processes and volatile compounds perform an important role in contributing to the quality of wines. ‘Marselan’ is a red grape variety grown in several countries such as France, Brazil and China. This variety has gained international interest in recent years. The volatile profile of Brazilian ‘Marselan’ red wines during various winemaking processes was studied. Four processes were applied: thermovinification, integrale vinification, classic winemaking and classic winemaking pretreated with ultrasound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 29 publications
0
12
1
3
Order By: Relevance
“…However, the concentration of acetates (isoamyl acetate, hexyl acetate) decreased or remained constant in wines made from sonicated grapes at both maceration times. In studies carried out by other authors, when US is applied during the grape maceration, lower production of acetates was observed, while the total esters remained constant or increased, depending on the treatment conditions [ 26 , 32 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the concentration of acetates (isoamyl acetate, hexyl acetate) decreased or remained constant in wines made from sonicated grapes at both maceration times. In studies carried out by other authors, when US is applied during the grape maceration, lower production of acetates was observed, while the total esters remained constant or increased, depending on the treatment conditions [ 26 , 32 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ruiz-Rodriguez et al [ 32 ], observed better scores in fruity and floral aroma in wines from Syrah grapes sonicated during maceration, while Cui et al [ 31 ], reported more complex aromas only in white wines sonicated for short times. The sensory evaluation of red wines elaborated with thermovinification and with US treatment was similar, obtaining greater aromatic complexity and perception of fruit aromas than the control wine [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The effect of other grape maceration techniques on the sensory perception of wines differs according to the studies carried out. Maceration with ultrasound and thermovinification increased floral and fruity scores, obtaining greater aromatic complexity in Syrah and Monastrell wines [ 15 , 16 , 46 ]. No defect or unpleasant aromas were detected in the wines analyzed, which has been described with other intensive maceration techniques [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Today Marselan wines are interesting to researchers [48][49][50]. Aroma profiles of Marselan wines made by different wine technologies in Brazil consisted of plum, strawberry, red fruits, blackberry, cherry, tropical fruits, raisin, honey, and marmalade aromas.…”
Section: Sensory Analysismentioning
confidence: 99%
“…Aroma profiles of Marselan wines made by different wine technologies in Brazil consisted of plum, strawberry, red fruits, blackberry, cherry, tropical fruits, raisin, honey, and marmalade aromas. In addition, vegetable properties such as bell pepper, string bean, dry straw, with, broccoli, asparagus, cabbage, pepper, twig, and spicy aromatic descriptors including pepper, mint, clove, cinnamon, mushroom, nutmeg, fine herbs, vanilla, and chocolate occur in small quantities [48]. According to our observations, Marselan icewine of both harvests possessed plum, cherry, raisin, honey, and dried apricot aromas; however, in samples which had been produced from H2, these descriptors were more intense (p ≤ 0.05).…”
Section: Sensory Analysismentioning
confidence: 99%